2023
DOI: 10.2196/40955
|View full text |Cite
|
Sign up to set email alerts
|

Stop and Play Digital Health Education Intervention for Reducing Excessive Screen Time Among Preschoolers From Low Socioeconomic Families: Cluster Randomized Controlled Trial

Abstract: Background High prevalence of excessive screen time among preschool children is attributable to certain parental factors such as lack of knowledge, false perception about screen time, and inadequate skills. Lack of strategies to implement screen time guidelines, in addition to multiple commitments that may hinder parents from face-to-face interventions, demands the need to develop a technology-based parent-friendly screen time reduction intervention. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…There are n=3 studies found in Pakistan [24], [26], [28] suggesting a growing awareness of the importance of understanding children's screen time in the country. Four countries -Germany [19], [22], Malaysia [30], [44], Ireland [21], [34] and United Kingdom [12], [27] share a similar number of studies with n=2. Meanwhile, ten countries, namely Sri Lanka [31], France [32], Saudi Arabia [23], China [37], Australia [9], Portugal [35], Poland [13], Italy [25], Norway [14], Iran [45] and a combination of multiple European countries [16] recorded with one study each.…”
Section: Distribution Of Past Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…There are n=3 studies found in Pakistan [24], [26], [28] suggesting a growing awareness of the importance of understanding children's screen time in the country. Four countries -Germany [19], [22], Malaysia [30], [44], Ireland [21], [34] and United Kingdom [12], [27] share a similar number of studies with n=2. Meanwhile, ten countries, namely Sri Lanka [31], France [32], Saudi Arabia [23], China [37], Australia [9], Portugal [35], Poland [13], Italy [25], Norway [14], Iran [45] and a combination of multiple European countries [16] recorded with one study each.…”
Section: Distribution Of Past Studiesmentioning
confidence: 99%
“…Meanwhile, n=6 studies used a mixed-method research design. This review indicates that the survey is the highest research approach used for collecting data on screen time behaviours with n=15 [12], [16]- [19], [22], [23], [25], [27], [30], [32], [34], [38], [40], [44], In addition, the cross-sectional study indicates n=8 studies [28], [29], [31], [23], [35], [24], [41], [26] and interviews with n=5 studies [20], [12], [23], [43], [45] respectively. Meanwhile, n=3 studies [14], [21], [37], were found to apply the longitudinal study and n=2 studies used the descriptive study [17], [36] respectively.…”
Section: Research Design Used In Past Studiesmentioning
confidence: 99%
See 3 more Smart Citations